Pengaruh Lama Pelayuan dan Penyulingan Terhadap Rendemen serta Karakteristik Minyak Serai Wangi (Cymbopogon nardus L.) - Rina Sardillah Mae; MM Endah Mulat Satmalawati; Jefrianus Nino (Universitas Atma Jaya Yogyakarta, 2026)
(Cymbopogon nardus L.) is an important commodity with high economic value, but its quality and yield are greatly influenced by post-harvest processes. This study aims to determine the effect of withering and distillation on the yield, quality, and characteristics of citronella oil. The study was conducted using a Completely Randomized Design (CRD) with two variables, namely withering (1, 2, and 3 days) and distillation (2, 4, and 6 hours). The parameters observed were oil content, specific gravity, refractive index, solubility in 80% ethanol, and sensory assessments related to color and aroma. The duration of withering and distillation time had a significant effect on the quantity of citronella oil. The best oil yield of 0.8% was obtained from a three-day withering process with a six-hour distillation time, while the lowest yield of 0.5% was obtained from a one-day withering process and a two-hour distillation. The resulting parameter values include specific gravity (0.893–0.899 g/mL), refractive index (1.467–1.470), and solubility (1:2), all of which meet the standard requirements set by SNI 06-3953-1995. Sensori- cally, the oil is pale yellow to brownish in color with a distinctive lemongrass aroma and is acceptable to the panelists.